The Application of Andrographis Paniculata Gel as an Adjunct in The Treatment of Chronic Periodontitis : Clinical and Microbiological Effects - Thawornrungroj, Suwalee; Kuphasuk, Yosvimol; Petmitr, Songsak; Srisatjaluk, Ratchapin; Kitkumthorn, Nakarin (Asian Health, Science and Technology Reports, 2011)
The purpose of this study was to evaluate the clinical and microbiological effects of locally delivered Andrographis paniculata (AP) gel as an adjunct to scaling and root planing (SRP) in the treatment of chronic periodontitis. Thirty- two systemically healthy and non-smoking subjects with chronic periodontitis were recruited in this study. The subjects had to comply with the following criteria; having three single-rooted teeth located in different quadrants with probing pocket depth 5 mm and bleeding on probing, no history of receiving periodontal therapy or antibiotics within 6 months. The experimental sites of three teeth of each subject were randomly assigned to receive either of the three treatments; SRP plus AP gel, SRP plus gel base, or SRP only. The gels were applied at day 0, 1, 2, 3 weeks. Four clinical parameters, i.e., probing pocket depth, clinical attachment level, gingival index, and bleeding on probing were recored at day 0 (baseline), 1 and 3 months after treatments. Subgingival plaque was also taken using paper points at the same time points and subjected to the real-time PCR method (EvaGreen) for quantification of Porphyromonas gingivalis. Results showed that clinical changes at the disease sites were significantly improved after received all three treatments (p<0.05). When compared the clinical outcomes among the treatments. The clinical outcomes of the SRP plus AP gel-treated sites significantly showed a better improvement (p<0.05). For microbiological study, P. gingivalis was detected only in eight subjects at baseline. After treatment for 3 months, the bacteria could not be detected in five subjects. In conclusion, the local application of AP gel as an adjunct to SRP showed a better improvement of clinical parameters. These results indicated the benefit of AP gel as an adjunct in the treatment of chronic periodontitis.